Analysis of the Role of Assertive Communication Styles in Improving Organizational Performance - Ahmad Turmuzi; Andini Valentina; Tetti Saidah Siregar (Journal of Global Islamic Economic Studies, 2024)
Communication is a fundamental element in modern organizational management. One of the most effective forms of communication in the work environment is assertive communication, which is the ability of individuals to express opinions, feelings, and needs in an honest, open manner, and while respecting the rights of others. This study aims to analyze the role of assertive communication styles in improving organizational performance, especially in the context of work relations, team effectiveness, and its contribution to productivity and well-being. The discussion in this article reviews two main aspects: first, the definition and characteristics of assertive communication styles in organizations; and second, how this communication style contributes to improving organizational performance. Assertive communication has been proven to be able to create a healthy work climate, minimize conflicts, speed up the decision-making process, and strengthen individual confidence and responsibility. In the long run, an assertive communication culture encourages the creation of an adaptive, inclusive, and solution-oriented organization. Leaders and employees who adopt an assertive communication style show improvements in work effectiveness, conflict management, and the ability to build harmonious working relationships. Additionally, organizations that build systems and policies that support open and assertive communication tend to have higher work performance. Thus, assertive communication not only serves as an interpersonal strategy, but also as an important foundation in building organizational excellence in a sustainable manner. The implications of this study emphasize the importance of assertive communication training and the formation of an organizational culture that encourages healthy and constructive self-expression.